“Age Related Differences in the Biology of Chronic Graft-Versus-Host Disease After Hematopoietic Stem Cell Transplantation” - Cuvelier, Geoff D. E.; Li, Amanda; Drissler, Sibyl; Kariminia, Amina; Abdossamadi, Sayeh; Rozmus, Jacob; Chanoine, Jean-Pierre; Ng, Bernard; Mostafavi, Sara; Brinkman, Ryan R.; Schultz, Kirk R. (Frontiers in Immunology, 2020)
It is well established that pediatric recipients have a lower rate of cGvHD and lower severity. For a long time, it has been hypothesized that thymic function is the primary reason for the lower rate cGvHD yet there is little human evidence after HSCT to support this hypothesis. Comprehensive immune profiling by our group of both cellular and plasma markers evaluations finds similarities and differences in both adults and pediatric population. Our pediatric cohort was large enough to allow for a sub analysis of the impact of puberty in children aged 0 – 12 compared to ≥12 – 18 years. We found that there were significant differences between children and adults with an increase in PD1- naïve and memory Th cell populations consistent with a predominance of peripheral tolerance whereas prepubertal children had decreases in recent thymic emigrant (RTE) naïve Th and Treg populations supporting the importance of central tolerance induction in that population. We saw a significant suppression of newly formed B cell populations in children where as there appears to be a defect in an early B cell check point inhibition in adults with an increase in T1-CD21lo B cells and a decrease in T1-CD24hiCD38hi B cells. While ST2 elevation and NKreg decreases were seen in all ages groups that develop cGvHD, aminopeptidase N (sCD13) elevation was only seen in prepubertal children suggesting a role in broad suppression of B cell and thymopoiesis. We discuss the possible mechanisms for these age related differences and how this may impact on therapeutic approaches to cGvHD.